A revision of the European species of Calodera Mannerheim (Coleoptera: Staphylinidae, Aleocharinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 1996)
The types and further material of the European species of Calodera Mannerheim, 1831 are revised. 10 valid species are recognized: C. nigrita Mannerheim, C. protensa Mannerheim, C. lapponica J. Sahlberg, C. uliginosa Erichson, C. riparia Erichson, C. rufescens Kraatz, C. aethiops (Gravenhorst), C. cochlearis sp. n., C. stiliformis sp. n. and C. ligula sp. n. Lectotypes are designated for C. nigrita, C. protensa, C. lapponica, C. uliginosa, C. riparia, C. rufescens, C. aethiops and C. paludum Kraatz. C. paludum Kraatz, a former synonym of C. riparia, is synonymized with C. rufescens Kraatz. The synonymy of C. humilis Erichson with C. protensa is confirmed. - The descriptions of the species are supplemented by figures of the male genitalia, notes on distribution and bionomics, and a diagnostic key. Keywords Coleoptera, Staphylinidae, Aleocharinae, Calodera, Palaearctic, Europe, taxonomy, revision, new species. Nomenclatural Acts aethiops (Gravenhorst, 1802) (Calodera), Lectotype described as Aleochara aethiops cochlearis Assing, 1996 (Calodera), spec. n. lapponica J. Sahlberg, 1876 (Calodera), Lectotype ligula Assing, 1996 (Calodera), spec. n. nigrita Mannerheim, 1831 (Calodera), Lectotype paludum Kraatz, 1858 (Calodera), Lectotype; syn. n. of Calodera rufescens Kraatz, 1856 protensa Mannerheim, 1831 (Calodera), Lectotype riparia Erichson, 1837 (Calodera), Lectotype rufescens Kraatz, 1856 (Calodera), Lectotype stiliformis Assing, 1996 (Calodera), spec. n. uliginosa Erichson, 1837 (Calodera), Lectotype